Using nanosphere lithography for fabrication of a multilayered system of ordered gold nanoparticles - V.I. Styopkin; V. Liakhovetskyi; V. Rudenko (Semiconductor Physics, Quantum Electronics & Optoelectronics, 2017)
New modification of nanosphere lithography has been realized to obtain multilayered systems of ordered gold nanopartciles (NP). NP have been formed using vacuum deposition of 5…60-nm layer of gold on ionic etched multilayered regular coating consisted of several layers of 200-nm polystyrene spheres. Optical study shows that spectra of NP depend on their thickness and may be changed by heat treatment. Increasing the NP thickness within the 5…20-nm range leads to a shortwave displacement of the plasmon resonance peak position, while the longwave shift is observed in 20…60-nm range. Heat treatment of NP brings narrowing and displacement of spectral bands, rising the extinction. It has been supposed that variation of the NP shape is the most substantial factor for changes of optical properties in the 5…20 nm thickness region, while electromagnetic coupling between NP in different layers becomes more important for thicknesses larger than 40 nm. Optical properties inherent to the obtained system of NP can be tuned by changing the polystyrene spheres diameter, extent of etching, thickness of gold layer and with the heat treatment. It may be used in design of nanophotonic devices.